PENCIPTAAN BUKU ILUSTRASI PAKAIAN ADAT BREGADA HADININGRAT KRATON YOGYAKARTA SEBAGAI UPAYA PENGENALAN PAKAIAN TRADISIONAL KEPADA ANAK-ANAK - Yunanto, Agung Tri; Fianto, Achmad Yanu Alif; Hidayat, Wahyu (Jurnal Art Nouveau, 2015)
Abstract: Indonesia has a very diverse cultural treasures ranging  from customs artwork. In addition, Indonesia  consists of  several tribes that have cultural distinctiveness. Traditional Indonesian  clothing is one of the cultural property owned by the Indonesian state and recognized by other countries. One of  them is the Kasultanan Hadiningrat Yogyakarta which still preserve or perform ritual customs. One of the works of art and culture, one of which is still done until now is wearing traditional clothing. Traditional clothes of Yogyakarta is not only owned by the descendants of the royal nobles, but also owned by the courtiers and royal soldiers. To introduce custom clothing bregada Hadiningrat Kraton Yogyakarta then carried creation illustrated book as an attempt to introduce traditional clothing to children. To make this illustrated book uses several methods that begins with the collection of data from observation, interview and getting the data needed, and proceed with the creation of graphic design  elements. From this process resulted in an illustrated book that can describe the character of bregada Hadiningrat Kraton Yogyakarta. Illustration Book is needed here is a  illustration book using 2-dimensional concept that is able to attract the attention of the public to have characteristics of bregada Hadiningrat Kraton Yogyakarta itself. This is shown as an effort to support the introduction of the traditional clothing to the people, especially children. Keywords: Illustration book, Traditional clothing, Bregada, Kraton, Yogyakarta.